PENGARUH MOTIVASI, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN WARUNG MINA PEGUYANGAN DI DENPASAR - Indah Mariani, Luh Mang; Sariyathi, Ni Ketut (E-Jurnal Manajemen; Vol 6 No 7 (2017), 2017)
ABSTRACT Employee performance is the cornerstone of human resources management as it is one of the factors that determine the success of the company. Employee performance should be improved in order to provide maximum results for the company. The purpose of this study to analyze the influence of motivation, communication and discipline on employee performance. This research was conducted in Warung Mina Peguyangan in Denpasar. The total sample of 63 employees, with a saturated sampling method (census). Data were collected through observation, interviews and questionnaires. Data analysis technique used is multiple linear regression. Based on the analysis that has been processed, shows that all hypothesis is accepted. Motivation positive and significant effect on employee performance Warung Mina Peguyangan in Denpasar, communication positive and significant effect on employee performance Warung Mina Peguyangan in Denpasar and discipline positive and significant effect on employee performance Warung Mina Peguyangan in Denpasar.
Keywords: motivation, communication, work discipline, employee performance